2021
DOI: 10.1038/s41598-021-95637-9
|View full text |Cite
|
Sign up to set email alerts
|

Mapping gene and gene pathways associated with coronary artery disease: a CARDIoGRAM exome and multi-ancestry UK biobank analysis

Abstract: Coronary artery disease (CAD) genome-wide association studies typically focus on single nucleotide variants (SNVs), and many potentially associated SNVs fail to reach the GWAS significance threshold. We performed gene and pathway-based association (GBA) tests on publicly available Coronary ARtery DIsease Genome wide Replication and Meta-analysis consortium Exome (n = 120,575) and multi ancestry pan UK Biobank study (n = 442,574) summary data using versatile gene-based association study (VEGAS2) and Multi-marke… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 69 publications
0
4
0
Order By: Relevance
“…DUSP13 was associated with the regulation of the MAPK signaling pathway after stress stimulation in cardiomyocytes [ 35 ]. The up-regulation of DUSP13 to cardiac stress contributed to coronary artery disease, a common cardiovascular comorbidity of COVID-19 [ 36 , 37 ]. UNC5A retrained virus replication through autophagy induction instead of apoptosis [ 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…DUSP13 was associated with the regulation of the MAPK signaling pathway after stress stimulation in cardiomyocytes [ 35 ]. The up-regulation of DUSP13 to cardiac stress contributed to coronary artery disease, a common cardiovascular comorbidity of COVID-19 [ 36 , 37 ]. UNC5A retrained virus replication through autophagy induction instead of apoptosis [ 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…In FAM177B , we identified a variant (I3S) that corresponded with increased risk (OR, 1.18) and has recently been associated with CAD in a gene‐based meta‐analysis along with the substitution Q523R in MST1R . 76 These data illustrate that the 79 candidate genes are clinically important by increasing or decreasing the relative risk of EOMI and reveal variants of potentially novel mechanistic interest.…”
Section: Resultsmentioning
confidence: 88%
“… 109 , 110 Our analyses showed that MST1R is connected in STRING to EPOR , a regulator of JAK2 (Figure 2E ), and contains a single nucleotide polymorphism that is directly associated with increased EOMI risk (R1335G; OR, 1.15; EA=43.52) (Figure 3B ). MST1R has recently been identified by gene‐based association tests for CAD, 76 and MST1R null mice have impaired nitric oxide levels and increased tissue damage in response to acute stress. 111 Third, DHX58 represents a previously reported yet understudied association in the context of CAD.…”
Section: Discussionmentioning
confidence: 99%
“…Because there is no standardization on MAGMA window size beyond the notion that a larger window size incorporates SNPs falling in cis-regulatory elements, we evaluated the impact of the most used window sizes on results (details in Methods) (M. J. Zhang et al 2022; Jia et al 2022; Watanabe et al 2017; Sobrin et al 2022; Hariharan and Dupuis 2021; Watanabe et al 2019; Skene et al 2018; Zhu and Stephens 2018; Finucane et al 2018). Different window sizes for RA analyses only changed the significance calls for 16 of the 77 cell clusters in at least one of the window-sizes, half of which are only different in one window size (Figure 5).…”
Section: Resultsmentioning
confidence: 99%